2018
DOI: 10.1002/fsn3.904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some quality parameters of cassava starch and soy protein isolate matrices during deep fat frying in soybean oil

Abstract: Snack industry is recently focused on the production of snacks with minimal oil content and enhanced quality attributes which prompted the need to study the changes in snack matrices produced from cassava starch processed from three varieties of cassava roots (TMS‐950289, TME‐419, and TMS‐30572) and soy protein isolate blends fried in soybean oil. Effect of frying temperature (170–180°C), frying time (2–4 min), soy protein isolate inclusion level (5%–15%) on proximate composition, color changes, expansion, tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…A similar frying temperature effect on fried product moisture content has been reported by Omidiran et al. (2018).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…A similar frying temperature effect on fried product moisture content has been reported by Omidiran et al. (2018).…”
Section: Resultssupporting
confidence: 87%
“…Maity et al (2014) found out that at 100℃, the moisture content of the resultant fried chips was lower than the chips processed at lower temperatures of 80℃ and 90℃. A similar frying temperature effect on fried product moisture content has been reported by Omidiran et al (2018).…”
Section: Moisture Contentsupporting
confidence: 85%
See 1 more Smart Citation
“…The use of palmolein oil in frying snacks has been identified as a good oil as it does not emit undesirable odour, is highly resistant to oxidation, does not contain linolenic acid and has a favourable nutritional composition for being free of trans fatty acids and presenting tocopherols in its composition (Basiron, 2005). Omidiran et al (2019) reported some findings on some characteristics of these formulated snacks deep fried in soybean oil. Hence, the objective of the study is to assess and optimize the quality attributes of fried snacks from cassava starch of different varieties and soy protein isolate (SPI) blends using palmolein oil.…”
Section: Introductionmentioning
confidence: 99%